A kind of thioacetal polymer and its preparation method and application

Through the sulfur -aldehydes -shrinkable polymer prepared by sulfurization diol and tetron (alkyroxyl) glyphosate reactions, the problem of low refractive index and etching rate of existing anti -reflex coatings compositions, significantly improved, significantly improved Its application performance in the field of light glue.

CN115947913BActive Publication Date: 2025-01-28XIAMEN HENGKUN NEW MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310094446.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-10
Publication Date
2025-01-28
Estimated Expiration
2043-02-10

AI Technical Summary

Technical Problem

Existing bottom anti-reflective coating compositions containing glycoururide self-curing crosslinked polymers have problems with low refractive index and etching rates in the field of photoresist, which limits their application performance.

Method used

The sulfurization of sulfurization diol and tetanotoxyl glycerin is used to react reactions to prepare a sulfur sulfurization polymer with a specific structure to be used as the main component of anti -reflex coating compositions.

Benefits of technology

It improves the refractive index and etching rate of anti -reflector coating compositions, and enhances its application performance in the field of optical glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004071245130000021
    Figure BDA0004071245130000021
  • Figure BDA0004071245130000031
    Figure BDA0004071245130000031
  • Figure BDA0004071245130000032
    Figure BDA0004071245130000032
Patent Text Reader

Abstract

The invention belongs to the field of photolithography, and relates to a thioacetal polymer and a preparation method and application thereof. The thioacetal polymer comprises a structural unit derived from thioacetal diol and a structural unit derived from tetra(alkoxyalkyl) glycoluril. An anti-reflective coating composition containing the thioacetal polymer provided by the invention has both a high refractive index and an excellent etching rate, and has great industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photolithography and relates to a thioacetal polymer and a preparation method and application thereof. Background Art

[0002] Photoresist, also known as photoresist, is a photosensitive composition that can be used to transfer an image to a substrate. The photoresist coating composition is first applied to the substrate, and then the photoresist coating is exposed to an activating radiation source through a photomask. After exposure, photoinduced changes or chemical changes will occur on the photoresist. The photomask has areas that are transparent to the activating radiation and other areas that are opaque to the activation. Therefore, the photomask pattern will be transferred to the photoresist coating composition, and then the photoresist is developed to form a patterned image that can selectively process the substrate.

[0003] Semiconductor and integrated circuit manufacturing is achieved by micro-etching photoresist. As the requirements for photoresist resolution become higher and higher, the exposure wavelength continues to shorten, which promotes the application of deep ultraviolet exposure technology. Exposure plays a key role in high-resolution photoresist images. In the 248nm and 193nm lithography processes, the effect of the reflection of radiation from the substrate and the interference of the incident light becomes more and more obvious, and the standing wave effect formed inside the photoresist becomes more and more obvious, resulting in the photoresist not being able to be uniformly exposed, and the side walls of the pattern have wave-like jagged defects, resulting in uneven line width of the photoresist, and the design size difference cannot be controlled. These problems ultimately cause short circuits and open circuits of the lines, and ultimately affect the yield of the lithography process.

[0004] Studies have shown that coating an anti-reflective coating composition (BARC) between the photoresist and the substrate is the best choice for solving the above problems. It can effectively eliminate the interference standing wave effect formed by light reflection, reduce the non-uniformity of the photoresist line width, and enhance the influence on the uniformity of the key dimension. Usually, the anti-reflective coating composition is applied to the substrate, and then the photoresist is applied on the anti-reflective coating composition, and then the photoresist is exposed, developed, and etched, so that the photoresist pattern is transferred to the substrate. At present, semiconductor and integrated circuit manufacturers are still working hard to improve the resolution of the photoresist pattern, so higher requirements are put forward for the performance of the anti-reflective coating composition. At present, glycoluril self-curing cross-linked polymers are often used in anti-reflective coating compositions, but due to their poor stability, the refractive index and etching rate also have low defects, which greatly limits their application in the field of photoresists. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the existing bottom anti-reflective coating composition containing glycoluril self-curing cross-linking polymer, such as low refractive index and low etching rate, and to provide a thioacetal polymer and a preparation method and application thereof. The bottom anti-reflective coating composition containing the thioacetal polymer has a high refractive index and high etching rate.

[0006] Specifically, the present invention provides a thioacetal polymer, wherein the thioacetal polymer comprises a structural unit derived from a thioacetal diol as shown in formula (1) and a structural unit derived from a tetra(alkoxyalkyl) glycoluril as shown in formula (2);

[0007]

[0008] In formula (1), R 1 Represents hydrogen, C 1 ~C 10 Substituted or unsubstituted alkyl, C 3 ~C 20 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 A substituted or unsubstituted aromatic group, wherein n represents an integer of 1 to 10;

[0009] In formula (2), R 2 , R 3 , R 4 and R 5 Each independently represents -(CH 2 ) a -O-(CH 2 ) b -CH 3 , a is an integer from 1 to 6, b is an integer from 0 to 6; R 6 and R 7 Each independently represents hydrogen or C 1 ~C 10 A substituted or unsubstituted alkyl group.

[0010] In a preferred embodiment, the molar ratio of the structural unit derived from the thioacetal diol represented by formula (1) to the structural unit derived from the tetra(alkoxyalkyl) glycoluril represented by formula (2) is (0.1-0.9):1.

[0011] In a preferred embodiment, the weight average molecular weight Mw of the thioacetal polymer is 2000-12000 Daltons, and the polydispersity PDI is 1.5-2.5.

[0012] The present invention also provides a method for preparing a thioacetal polymer, which comprises subjecting a thioacetal diol represented by formula (1) to a condensation polymerization reaction with a tetra(alkoxyalkyl) glycoluril represented by formula (2);

[0013]

[0014] In formula (1), R 1 Represents hydrogen, C 1 ~C 10 Substituted or unsubstituted alkyl, C 3 ~C 20 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 A substituted or unsubstituted aromatic group, wherein n represents an integer of 1 to 10;

[0015] In formula (2), R 2 , R 3 , R 4 and R 5 Each independently represents -(CH 2 ) a -O-(CH 2 ) b -CH 3 , a is an integer from 1 to 6, b is an integer from 0 to 6; R 6 and R 7 Each independently represents hydrogen or C 1 ~C 10 A substituted or unsubstituted alkyl group.

[0016] In a preferred embodiment, the thioacetal diol is obtained by condensing the aldehyde compound represented by formula (3) with the mercapto alcohol represented by formula (4) in the presence of a catalyst;

[0017]

[0018] In formula (3), R 1 Represents hydrogen, C 1 ~C 10 Substituted or unsubstituted alkyl, C 3 ~C 20 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 a substituted or unsubstituted aromatic group;

[0019] In formula (4), n represents an integer of 1 to 10.

[0020] In a preferred embodiment, the molar ratio of the aldehyde compound to the mercapto alcohol is 1:(2-2.5).

[0021] In a preferred embodiment, the catalyst is NiCl 2· 6H 2 O.

[0022] In a preferred embodiment, the amount of the catalyst used is 0.5-2% of the total weight of the aldehyde compound and the mercapto alcohol.

[0023] In a preferred embodiment, the condensation reaction conditions include a temperature of 20 to 35° C. and a time of 1 to 2 hours.

[0024] In a preferred embodiment, the conditions of the polycondensation reaction include a temperature of 80 to 100° C. and a time of 2 to 10 hours.

[0025] The present invention also provides a thioacetal polymer prepared by the method.

[0026] The present invention also provides application of the thioacetal polymer in the field of photolithography.

[0027] The key of the present invention is to carry out polycondensation reaction of thioacetal diol with specific structure and tetra(alkoxyalkyl) glycoluril, so that the obtained thioacetal polymer can improve the refractive index and etching rate when applied to the bottom anti-reflective coating composition. DETAILED DESCRIPTION

[0028] The present invention will be described in detail below through examples.

[0029] The thioacetal polymer provided by the present invention is a polymer obtained by polycondensation of thioacetal diol and tetra(alkoxyalkyl) glycoluril, that is, it includes structural units derived from thioacetal diol and structural units derived from tetra(alkoxyalkyl) glycoluril. Among them, the molar ratio of the structural units derived from thioacetal diol to the structural units derived from tetra(alkoxyalkyl) glycoluril is preferably (0.1-0.9):1, preferably (0.2-0.8):1, such as 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1 and any value therebetween.

[0030] In the present invention, the thioacetal diol has a structure shown in formula (1):

[0031]

[0032] In formula (1), R 1 Represents hydrogen, C 1 ~C 10 Substituted or unsubstituted alkyl, C 3 ~C 20 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 The substituted or unsubstituted aromatic group preferably represents hydrogen, C 1 ~C 5 Substituted or unsubstituted alkyl, C 6 ~C10 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 In the present invention, C 1 ~C 5 Specific examples of substituted or unsubstituted alkyl groups include, but are not limited to, substituted or unsubstituted methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl or neopentyl. 6 ~C 10 Specific examples of substituted or unsubstituted cycloalkyl include, but are not limited to, substituted or unsubstituted cyclohexyl, methylcyclohexyl, ethylcyclohexyl, cyclopentyl or methylcyclopentyl. 6 ~C 20 Specific examples of the substituted or unsubstituted aromatic group include, but are not limited to, substituted or unsubstituted phenyl, tolyl, ethylphenyl or naphthyl. n represents an integer of 1 to 10, such as 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0033] In the present invention, the tetra(alkoxyalkyl) glycoluril has a structure shown in formula (2):

[0034]

[0035] In formula (2), R 2 , R 3 , R 4 and R 5 Each independently represents -(CH 2 ) a -O-(CH 2 ) b -CH 3 , a is an integer of 1 to 6, such as 1, 2, 3, 4, 5 or 6; b is an integer of 0 to 6, such as 0, 1, 2, 3, 4, 5 or 6. R 6 and R 7 Each independently represents hydrogen or C 1 ~C 10 Substituted or unsubstituted alkyl, preferably hydrogen or C 1 ~C 5 A substituted or unsubstituted alkyl group.

[0036] In the present invention, the weight average molecular weight Mw of the thioacetal polymer is preferably 2000-12000 Daltons, more preferably 3000-10000 Daltons, such as 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000 and any value therebetween; the polydispersity PDI is preferably 1.5-2.5, more preferably 1.5-2.2, such as 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2 and any value therebetween.

[0037] The preparation method of the thioacetal polymer provided by the present invention comprises polycondensing thioacetal diol and tetra(alkoxyalkyl) glycoluril, wherein the specific structures of the thioacetal diol and tetra(alkoxyalkyl) glycoluril are shown above and will not be described in detail here.

[0038] The thioacetal diol can be prepared according to various existing methods. In a preferred embodiment, the thioacetal diol is obtained by condensing the aldehyde compound represented by formula (3) with the mercapto alcohol represented by formula (4) in the presence of a catalyst;

[0039]

[0040] In formula (3), R 1 Represents hydrogen, C 1 ~C 10 Substituted or unsubstituted alkyl, C 3 ~C 20 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 The substituted or unsubstituted aromatic group preferably represents hydrogen, C 1 ~C 5 Substituted or unsubstituted alkyl, C 6 ~C 10 Substituted or unsubstituted cycloalkyl or C 6 ~C 20 A substituted or unsubstituted aromatic group; in formula (4), n represents an integer of 1 to 10.

[0041] In the preparation process of the above-mentioned thioacetal diol, the molar ratio of the aldehyde compound to the mercapto alcohol is preferably 1:(2-2.5), such as 2, 2.1, 2.2, 2.3, 2.4, 2.5 and any value therebetween.

[0042] In the preparation process of the above-mentioned thioacetal diol, the catalyst used is preferably NiCl 2· 6H 2The amount of the catalyst is preferably 0.5-2% of the total weight of the aldehyde compound and the mercapto alcohol, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2.0% and any value therebetween.

[0043] In the preparation process of the above-mentioned thioacetal diol, the conditions of the condensation reaction preferably include a temperature of 20 to 35°C, such as 20°C, 22°C, 25°C, 28°C, 30°C, 32°C, 35°C and any value therebetween; and a time of 1 to 2h, such as 1h, 1.2h, 1.5h, 1.8h, 2h and any value therebetween.

[0044] In the preparation process of the above-mentioned thioacetal polymer, the conditions of the condensation reaction preferably include a temperature of 80 to 100°C, such as 80°C, 82°C, 85°C, 88°C, 90°C, 92°C, 95°C, 98°C, 100°C and any value therebetween; and a time of 2 to 10h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any value therebetween.

[0045] In the preparation process of the above thioacetal polymer, the polycondensation reaction generally needs to be carried out in the presence of p-toluenesulfonic acid and an organic solvent.

[0046] The present invention also provides a thioacetal polymer prepared by the method.

[0047] In addition, the present invention also provides the application of the thioacetal polymer in the field of photolithography. In a specific application process, the anti-reflection coating composition containing the thioacetal polymer is applied to a substrate and heat-treated to form a bottom anti-reflection coating on the substrate, and then a photoresist resist is formed on the bottom anti-reflection coating, and then the photoresist resist is exposed and developed to form a photoresist pattern. The key point of the present invention is to adopt a new thioacetal polymer as the main component of the anti-reflection coating composition, and other components and their contents can be conventionally selected in the art, and those skilled in the art can all know this, and will not be repeated here.

[0048] The present invention is explained in more detail below with reference to Examples and Comparative Examples.

[0049] Preparation Example 1 Preparation of Thioacetal Diol

[0050] Acetaldehyde (0.2 mol, 8.81 g) and 2-mercaptoethanol (0.4 mol, 31.25 g) were mixed evenly and then the catalyst NiCl was added. 2 6H 2O (0.001 mol, 0.24 g) was continued to be mixed evenly, and then the resulting solution was stirred for reaction at 35 ° C for 1 hour, and then 100 mL of dichloromethane was added to separate the catalyst by filtration, and then the resulting liquid product was concentrated by vacuum distillation and purified by silica gel (200-300 mesh) column chromatography to obtain the thioacetal diol compound A1 shown in formula (5), which is a white solid.

[0051] According to infrared detection, at 3300-3400cm -1 There are two characteristic peaks of -OH nearby.

[0052] Through nuclear magnetic resonance testing, 1 H-NMR (400MHz, CDCl 3 )δ(ppm)3.7(s,1H,-SCHS-),3.45(t,J=5.0Hz,4H,-CH 2 OH), 2.86-2.62(m,4H,-CH 2 CH 2 OH),1.5(s,3H,-CH 3 ). This indicates that the thioacetal diol compound A1 indeed has the structure shown in formula (5).

[0053]

[0054] Preparation Example 2 Preparation of Thioacetal Diol

[0055] Benzaldehyde (0.2 mol, 21.22 g) and 2-mercaptoethanol (0.4 mol, 31.25 g) were mixed evenly and then the catalyst NiCl was added. 2 6H 2 O (0.001 mol, 0.24 g) was continued to be mixed evenly, and then the resulting solution was stirred for reaction at 20° C. for 2 hours, and then 100 mL of dichloromethane was added to separate the catalyst by filtration. The resulting liquid product was then concentrated by vacuum distillation and purified by a silica gel (200-300 mesh) column to obtain the thioacetal diol compound A2 shown in formula (6), which was a white solid.

[0056] According to infrared detection, at 3300-3400cm -1 There are two characteristic peaks of -OH nearby.

[0057] Through nuclear magnetic resonance testing, 1 H-NMR (400MHz, CDCl 3 )δ(ppm)7.66-7.3(m,4H,PhH),5.12(s,1H,-SCHS-),3.68(t,J=5.2Hz,4H,-CH 2OH), 2.95-2.65(m,4H,-CH 2 CH 2 OH). This indicates that the thioacetal diol compound A2 indeed has the structure shown in formula (6).

[0058]

[0059] Synthesis Example 1 Preparation of Thioacetal Polymer

[0060] At room temperature, 430g of tetramethoxymethyl glycoluril, 82g of thioacetal diol A1, 5.1g of p-toluenesulfonic acid and 880g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 2000mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 85°C, and the reaction timer was started when the reactants were completely dissolved and the reaction system began to reflux, and the reaction time was about 6 hours, and then the reaction solution was cooled to room temperature. The same amount of PGMEA was added to the mixed solution for dilution and shaken, the diluted reaction solution was slowly added to distilled water and stirred for 30 minutes, then allowed to stand for 10 minutes, the water was poured off, leaving a viscous solid, and the above operation was repeated 2 times, and then thoroughly washed with distilled water, and then 2 times the amount of PGMEA was added to the reaction input to dissolve and shake evenly, and the water was removed by reduced pressure distillation to obtain a thioacetal polymer, the weight average molecular weight Mw of the polymer was 6105, and the molecular weight distribution PDI was 2.04. H 1 NMR results showed that the polymer was a condensation product of two starting materials, among which the broad peak at 3.7 ppm was the characteristic peak of the methine (CH) of thioacetal diol A1, and the broad peak at 3.3 ppm was the characteristic peak of the unreacted methoxy (CH) of tetramethoxymethyl glycoluril. 3 O) characteristic peaks.

[0061] Synthesis Example 2 Preparation of Thioacetal Polymer

[0062] At room temperature, 444g of tetramethoxymethyl glycoluril, 114g of thioacetal diol A2, 5.6g of p-toluenesulfonic acid and 960g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 2000mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 85°C, and the reaction timer was started when the reactants were completely dissolved and the reaction system began to reflux, and the reaction time was about 4 hours, and then the reaction solution was cooled to room temperature. The same amount of PGMEA was added to the mixed solution for dilution and shaken, the diluted reaction solution was slowly added to distilled water and stirred for 30 minutes, then allowed to stand for 10 minutes, the distilled water was poured off, leaving a viscous solid, and the above operation was repeated 2 times, and then thoroughly washed with distilled water, and then 2 times the amount of PGMEA was added to the reaction input to dissolve and shake evenly, and the water was removed by reduced pressure distillation to obtain a thioacetal polymer, the weight average molecular weight Mw of the polymer was 4174, and the molecular weight distribution PDI was 1.82. H 1 NMR results showed that the polymer was a condensation product of two starting materials, among which the broad peak at 7.3 ppm was the characteristic peak of the benzene ring structure of thioacetal diol A2, and the broad peak at 3.3 ppm was the unreacted methoxy group (CH 3 O) characteristic peaks.

[0063] Synthesis Example 3 Preparation of Thioacetal Polymer

[0064] At room temperature, 330 g of tetramethoxymethyl glycoluril, 41 g of thioacetal diol A1, 71.5 g of thioacetal diol A2, 3.3 g of p-toluenesulfonic acid and 638 g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 1000 mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 80°C, and the reaction timer was started when the reactants were completely dissolved and the reaction system began to reflux, the reaction was carried out for about 5 hours, and then the reaction solution was cooled to room temperature. The same amount of PGMEA was added to the mixture to dilute and shake well. The diluted reaction solution was slowly added to distilled water and stirred for 30 minutes, then allowed to stand for 10 minutes, the distilled water was poured off, leaving the viscous solid, and the above operation was repeated twice. After that, it was thoroughly washed with distilled water, and then PGMEA in an amount twice the amount of the reaction input was added to dissolve and shake well. The water was removed by distillation under reduced pressure to obtain a thioacetal polymer. The weight average molecular weight Mw of the polymer was 5148, and the molecular weight distribution PDI was 1.93. 1 NMR results showed that the polymer was a condensation product of three starting materials, among which the broad peak at 7.3 ppm was the characteristic peak of the benzene ring structure of thioacetal diol A2, the broad peak at 3.7 ppm was the characteristic peak of the methine (CH) of thioacetal diol A1, and the broad peak at 3.3 ppm was the characteristic peak of the unreacted methoxy (CH) of tetramethoxymethyl glycoluril. 3O) characteristic peaks.

[0065] Synthesis Example 4 Preparation of Thioacetal Polymer

[0066] At room temperature, add 201g of tetramethoxymethyl glycoluril, 51g of thioacetal diol A2, 2.5g of p-toluenesulfonic acid and 433g of propylene glycol monomethyl ether acetate (PGMEA) to a 1000mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, heat to 100°C, and start the reaction timing when the reactants are completely dissolved and the reaction system begins to reflux, react for about 7 hours, and then cool the reaction solution to room temperature. Add the same amount of PGMEA to the mixed solution for dilution and shake well, slowly add the diluted reaction solution to distilled water and stir for 30 minutes, then let it stand for 10 minutes, pour the distilled water, leaving a viscous solid, repeat the above operation twice, then wash it thoroughly with distilled water, then add 2 times the amount of PGMEA to the reaction input to dissolve and shake evenly, and remove water by reduced pressure distillation to obtain a thioacetal polymer, the weight average molecular weight Mw of the polymer is 8965, and the molecular weight distribution PDI is 2.20. H 1 NMR results showed that the polymer was a condensation product of two starting materials, among which the broad peak at 7.3 ppm was the characteristic peak of the benzene ring structure of thioacetal diol A2, and the broad peak at 3.3 ppm was the unreacted methoxy group (CH 3 O) characteristic peaks.

[0067] Synthesis Example 5 Preparation of Thioacetal Polymer

[0068] At room temperature, 191 g of tetramethoxymethyl glycoluril, 27.4 g of thioacetal diol A1, 18.6 g of p-methoxyphenol, 2.4 g of p-toluenesulfonic acid and 376 g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 500 mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 80°C, and the reaction timer was started when the reactants were completely dissolved and the reaction system began to reflux, the reaction was continued for about 3 hours, and then the reaction solution was cooled to room temperature. The same amount of PGMEA was added to the mixed solution to dilute and shake well, the diluted reaction solution was slowly added to distilled water, stirred for 30 minutes, and then allowed to stand for 10 minutes, the distilled water was poured off, leaving the viscous solid, and the above operation was repeated twice, and then thoroughly washed with distilled water, and then PGMEA twice the amount of the reaction input was added to dissolve and shake well, and the water was removed by vacuum distillation to obtain a thioacetal polymer, the weight average molecular weight Mw of the polymer was 2986, and the molecular weight distribution PDI was 1.65. 1NMR results showed that the polymer was a condensation product of two starting materials, among which the broad peak at 3.7 ppm was the characteristic peak of the methine (CH) of thioacetal diol A1, and the broad peak at 3.3 ppm was the characteristic peak of the unreacted methoxy (CH) of tetramethoxymethyl glycoluril. 3 O) characteristic peaks.

[0069] Synthesis Example 6 Preparation of Thioacetal Polymer

[0070] At room temperature, 153 g of tetramethoxymethyl glycoluril, 29.3 g of thioacetal diol A2, 21.4 g of dimethyl tartrate, 2.0 g of p-toluenesulfonic acid and 314 g of propylene glycol monomethyl ether acetate (PGMEA) were added to a 500 mL three-necked flask equipped with a thermometer, a mechanical stirrer, a reflux condenser and a water separator; under nitrogen protection, the temperature was raised to 96 ° C, and the reaction timer was started when the reactants were completely dissolved and the reaction system began to reflux, the reaction was carried out for about 3 hours, and then the reaction solution was cooled to room temperature. The same amount of PGMEA was added to the mixed solution to dilute and shake well, the diluted reaction solution was slowly added to distilled water, stirred for 30 minutes, and then allowed to stand for 10 minutes, the distilled water was poured off, leaving the viscous solid, and the above operation was repeated twice, and then thoroughly washed with distilled water, and then PGMEA twice the amount of the reaction input was added to dissolve and shake well, and the water was removed by vacuum distillation to obtain a thioacetal polymer, the weight average molecular weight Mw of the polymer was 3762, and the molecular weight distribution PDI was 1.76. 1 NMR results showed that the polymer was a condensation product of two starting materials, among which the broad peak at 7.3 ppm was the characteristic peak of the benzene ring structure of thioacetal diol A2, and the broad peak at 3.3 ppm was the unreacted methoxy group (CH 3 O) characteristic peaks.

[0071] Preparation of Comparative Synthesis Example 1

[0072] The polymer was prepared according to the method of Synthesis Example 1, except that the thioacetal diol A1 was replaced by the same molar amount of 1,6-hexanediol. The other conditions were the same as those of Synthesis Example 1, to obtain polymer S1.

[0073] Preparation of Comparative Synthesis Example 2

[0074] The polymer was prepared according to the method of Synthesis Example 2, except that the thioacetal diol A2 was replaced by the same molar amount of 4-phenyl-1,7-heptanediol, and the other conditions were the same as those of Synthesis Example 2 to obtain polymer S2.

[0075] Preparation of Comparative Synthesis Example 3

[0076] The polymer was prepared according to the method of Synthesis Example 3, except that thioacetal diol A2 and thioacetal diol A3 were both replaced by the same molar amount of 4-phenyl-1,7-heptanediol, and the other conditions were the same as those of Synthesis Example 3 to obtain polymer S3.

[0077] Examples and Comparative Examples

[0078] The polymer, solvent, acid generator and additive were added to a clean bottle according to the ratio in Table 1, and the mixture was shaken until each component was completely dissolved, and then each sample was respectively passed through a 0.2 μm PTFE membrane filter and loaded into a new clean bottle to obtain a bottom anti-reflective coating composition. Among them, the solvent was OK73 (a mixed solvent obtained by mixing PGMEA and PGME in a volume ratio of 7:3), the acid generator was p-toluenesulfonic acid, and the additive was poly(hydroxystyrene-methyl methacrylate).

[0079] Table 1 (wt%)

[0080]

[0081] Test Case

[0082] The anti-reflective coating composition obtained in the above examples and comparative examples was spin-coated onto the etching layer of the silicon wafer, and then baked at 210° C. for 60 seconds to form a film with a thickness of The anti-reflection coating was tested for film thickness by a film thickness meter (purchased from KLA); the refractive index n of the anti-reflection coating was tested by an ellipsometer (purchased from Woollman) and the etching rate was tested by an etching device TE-8500P (purchased from TEL). The results are shown in Table 2.

[0083] Table 2

[0084] serial number Refractive index n Etching rate nm / s Example 1 1.87 13.7 Example 2 1.90 12.4 Example 3 1.89 12.9 Example 4 1.91 12.2 Example 5 1.88 13.3 Example 6 1.92 12.6 Comparative Example 1 1.77 8.9 Comparative Example 2 1.79 7.8 Comparative Example 3 1.78 8.4

[0085] From the comparison between the examples and the comparative examples, it can be seen that the anti-reflective coating composition containing the thioacetal polymer provided by the present invention has both high refractive index and excellent etching rate, and has great industrial application prospects.

[0086] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A thioacetal polymer, characterized in that The thioacetal polymer comprises a structural unit derived from a thioacetal diol as shown in formula (1) and a structural unit derived from a tetra(alkoxyalkyl) glycoluril as shown in formula (2); In formula (1), R1 represents hydrogen, C1 to C 10 Substituted or unsubstituted alkyl, C3~C 20 Substituted or unsubstituted cycloalkyl or C6~C 20 A substituted or unsubstituted aromatic group, wherein n represents an integer of 1 to 10; In formula (2), R2, R3, R4 and R5 each independently represent -(CH2) a -O-(CH2) b -CH3, a is an integer of 1 to 6, b is an integer of 0 to 6; R6 and R7 each independently represent hydrogen or C1 to C 10 A substituted or unsubstituted alkyl group.

2. The thioacetal polymer according to claim 1, characterized in that The molar ratio of the structural unit derived from the thioacetal diol represented by formula (1) to the structural unit derived from the tetra(alkoxyalkyl) glycoluril represented by formula (2) is (0.1 to 0.9):

1.

3. The thioacetal polymer according to claim 1, characterized in that The weight average molecular weight Mw of the thioacetal polymer is 2000-12000 Daltons, and the polydispersity PDI is 1.5-2.

5.

4. A method for preparing a thioacetal polymer, characterized in that: The method comprises subjecting the thioacetal diol represented by formula (1) to a polycondensation reaction with the tetra(alkoxyalkyl) glycoluril represented by formula (2); In formula (1), R1 represents hydrogen, C1 to C 10 Substituted or unsubstituted alkyl, C3~C 20 Substituted or unsubstituted cycloalkyl or C6~C 20 A substituted or unsubstituted aromatic group, wherein n represents an integer of 1 to 10; In formula (2), R2, R3, R4 and R5 each independently represent -(CH2) a -O-(CH2) b -CH3, a is an integer of 1 to 6, b is an integer of 0 to 6; R6 and R7 each independently represent hydrogen or C1 to C 10 A substituted or unsubstituted alkyl group.

5. The method for preparing a thioacetal polymer according to claim 4, characterized in that: The thioacetal diol is obtained by condensing an aldehyde compound represented by formula (3) with a mercapto alcohol represented by formula (4) in the presence of a catalyst; In formula (3), R1 represents hydrogen, C1 to C 10 Substituted or unsubstituted alkyl, C3~C 20 Substituted or unsubstituted cycloalkyl or C6~C 20 a substituted or unsubstituted aromatic group; In formula (4), n represents an integer of 1 to 10.

6. The method for preparing a thioacetal polymer according to claim 5, characterized in that: The molar ratio of the aldehyde compound to the mercapto alcohol is 1:(2-2.5); the catalyst is NiCl 2· 6H2O; the amount of the catalyst used is 0.5-2% of the total weight of the aldehyde compound and the mercapto alcohol.

7. The method for preparing a thioacetal polymer according to claim 5, characterized in that: The conditions of the condensation reaction include a temperature of 20 to 35° C. and a time of 1 to 2 hours.

8. The method for preparing a thioacetal polymer according to any one of claims 4 to 7, characterized in that: The conditions of the polycondensation reaction include a temperature of 80 to 100° C. and a time of 2 to 10 hours.

9. A thioacetal polymer prepared by the method according to any one of claims 4 to 8.

10. Use of the thioacetal polymer according to any one of claims 1 to 3 and 9 in the field of photolithography.

Citation Information

Patent Citations

  • Antireflective compositions for photoresists

    CN101027610A

  • Resist underlayer film-forming composition containing copolymer that has triazine ring and sulfur atom in main chain

    CN105849642A